COVID-19 and long-COVID thrombosis: from clinical and basic science to therapeutics - Violi, Francesco; Harenberg, Job; Pignatelli, Pasquale; Cammisotto, Vittoria (Thrombosis and haemostasis, 2023)
Coronavirus infectious disease-19 (COVID-19) is a pandemic characterized by serious lung disease and thrombotic events in the venous and circulation trees, which represent a harmful clinical sign of poor outcome. Thrombotic events are more frequent in patients with severe disease requiring intensive care units and are associated with platelet and clotting activation. However, after resolution of acute infection, patients may still have clinical sequelae, the so-called long-COVID-19, including thrombotic events again in the venous and arterial circulation. The mechanisms accounting for thrombosis in acute and long COVID-19 have not been fully clarified; interactions of COVID-19 with angiotensin converting enzyme 2 or toll-like receptor family or infection-induced cytokine storm have been suggested to be implicated in endothelial cells, leucocytes, and platelets to elicit clotting activation in acute as well in chronic phase of the disease. In acute COVID-19, prophylactic or full doses of anticoagulants exert beneficial effects even if the dosage choice is still under investigation; however, a residual risk still remains suggesting a need for a more appropriate therapeutic approach. In long COVID-19 preliminary data provided useful information in terms of antiplatelet treatment but definition of candidates for thrombotic prophylaxis is still undefined.